Within‐population genetic effects of mtDNA on metabolic rate in Drosophila subobscura. (6th January 2015) - Kurbalija Novičić, Z.; Immonen, E.; Jelić, M.; AnÐelković, M.; Stamenković‐Radak, M.; Arnqvist, G.
Abstract A growing body of research supports the view that within‐species sequence variation in the mitochondrial genome (mtDNA) is functional, in the sense that it has important phenotypic effects. However, most of this empirical foundation is based on comparisons across populations, and few studies have addressed the functional significance of mtDNA polymorphism within populations. Here, using mitonuclear introgression lines, we assess differences in whole‐organism metabolic rate of adult Drosophila subobscura fruit flies carrying either of three different sympatric mtDNA haplotypes. We document sizeable, up to 20%, differences in metabolic rate across these mtDNA haplotypes. Further, these mtDNA effects are to some extent sex specific. We found no significant nuclear or mitonuclear genetic effects on metabolic rate, consistent with a low degree of linkage disequilibrium between mitochondrial and nuclear genes within populations. The fact that mtDNA haplotype variation within a natural population affects metabolic rate, which is a key physiological trait with important effects on life‐history traits, adds weight to the emergent view that mtDNA haplotype variation is under natural selection and it revitalizes the question as to what processes act to maintain functional mtDNA polymorphism within populations.